Synthesis and Spectral Study of New Azo - Azomethine Dyes and its Copper (II) Complexes Derived from Resorcinol, 4-Aminobenzoylhydrazone and 4-Amino antipyrine - Jber, Nasreen R; Abood, Rana S; Al-Dhaief, Yasmeen A (Al-Nahrain Journal of Science, 2018)
Four new azo dyes L1, L2, L3 and L4, were prepared by linking benzaldehyde p-aminobenzoylhydrazone (3), p-hydroxybenzaldehyde p-amino- benzoylhydrazone (4), naphthaldehyde p-aminobenzoylhydrazone (5) and p-methoxybenzaldehyde p-aminobenzoylhydrazone (6) to resorcinol and through diazo-coupling reactions. Mixed-ligand dinuclear complexes with general stoichiometry [Cu2L(amino antipy.)2]Cl2 (11, 12, 13 and 14) was synthesed from azo ligands and bidentate ligand (4-aminoantipyrine) with copper. The structures of both azo dyes and their complexes were identified by elemental analyses (C.H.N), FTIR, 1H-NMR, UV-Vis, atomic absorbtion and magnetic susceptibility.